(3eYQaI CNJjGQGJ GdCjGe ef GdTghQ GdYQHjIs
(3ChdgG (B:s
(3aUd ai eYQaI GNJjGQGJ GdCjGe ef GdTghQ GdYQHjI hCfg UGdM Chd jhe ef GdTgQ UGdM dWdH GdMhGFL hGdJRhjL s
(3BNQgG (B:s
(3Gdjhe GdKdGKhf jhe UGdM ef SGaQ ajg Zfe aGYed eG JNJGQ aEfg UGdM dcd TF hGddg GYde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B149 - (3U(B151s
(3HgG fXGe GdJYbjHIs
(3fSNI HgG GdVHGW fGOQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs